Quantitative transportation assessment in simulated curved canals after large apical preparations - Vânia Cristina Gomes Vieira; Felipe Gonçalves Belladonna; Erick Miranda Souza; Gustavo De-Deus; Aline de Almeida Neves; Edson Jorge Lima Moreira; Emmanuel João Nogueira Leal Silva (Universidade Estadual de Campinas, 2017)
Aim: To evaluate the ability of rotary (ProTaper Universal [PTU] and ProTaper Next [PTN]), reciprocating (Reciproc [R] and WaveOne [WO]) and adaptive (Twisted File Adaptive [TFA]) systems in maintaining the original canal profile in straight and curved parts after apical preparations up to size 40. Methods: Resin blocks with simulated curved canals were randomly assigned to five groups: PTU, PTN, R, WO and TFA. Images were captured from each block before and after canal preparation (n=10). Assessment of canal transportation was obtained for the straight and curved parts of the canal. ANOVA followed by Tukey's test was used (α = 5%). Results: Transportation values were increased at the curved part (P = .00). For both canal levels, TFA system induced the lowest mean of canal transportation followed by PTN, R, WO and PTU systems. At the straight portion, transportation for R and TFA systems were similar (P > .05), and these values were significantly lower than for WO, PTN and PTU (P = .00). At the curved portion, TFA resulted in less canal transportation, followed by PTN, R, WO and PTU systems (P = .00). Conclusions: TFA system produced less canal transportation than other systems tested during large apical preparations.